2016
DOI: 10.1007/s10880-016-9471-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Humility and Hospital Safety Culture

Abstract: Hospital safety culture is an integral part of providing high quality care for patients, as well as promoting a safe and healthy environment for healthcare workers. In this article, we explore the extent to which cultural humility, which involves openness to cultural diverse individuals and groups, is related to hospital safety culture. A sample of 2011 hospital employees from four hospitals completed measures of organizational cultural humility and hospital safety culture. Higher perceptions of organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
2
18
0
4
Order By: Relevance
“…Beagan () proposed that cultural humility and cultural safety can both be measured by client‐reporting or the critical interrogation of providers regarding their own practice. In contrast, Hook and colleagues proposed that cultural humility and safety should only be measured through clients rating their providers and employees rating their agencies (Hook, Boan, et al, ; Hook, Watkins, et al, ).…”
Section: Shifting To Cultural Humility and Cultural Safetymentioning
confidence: 99%
“…Beagan () proposed that cultural humility and cultural safety can both be measured by client‐reporting or the critical interrogation of providers regarding their own practice. In contrast, Hook and colleagues proposed that cultural humility and safety should only be measured through clients rating their providers and employees rating their agencies (Hook, Boan, et al, ; Hook, Watkins, et al, ).…”
Section: Shifting To Cultural Humility and Cultural Safetymentioning
confidence: 99%
“…Hook study in the field of hospital safety culture in 6000 hospitals in the United States indicated that organizational learning and continuous improvement of processes are noticeable and significant to maintain the hospital safety culture [6]. Asefzadeh study on the risk assessment in Qazvin hospitals according to the World Health Organization model showed that the functional safety level is moderate in the hospitals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to identify potential capabilities and safety status of hospitals for involving them in response to emergencies [6]. Watson considered hospital safety as a crisis and believed that it is time to propose this important issue in the community and thereby, all responsible public health centers should provide important services to improve hospital safety and promote patient safety [7].…”
Section: Introductionmentioning
confidence: 99%
“…defined as a virtue that involves actively learning about others’ cultural experiences from them; Hook et al . ). Although women managers tend to show higher levels of passion for diversity, intercultural empathy, and diplomacy than men (Javidan et al .…”
Section: Gender Dandi From a Pwo Perspectivementioning
confidence: 97%
“…positive attitudes toward different others; Pittinsky and Montoya 2009), perspective-taking, and cultural humility (i.e. defined as a virtue that involves actively learning about others' cultural experiences from them; Hook et al 2016). Although women managers tend to show higher levels of passion for diversity, intercultural empathy, and diplomacy than men (Javidan et al 2016), these are useful skills that men might cultivate to bridge differences.…”
Section: Social Justice Morality and Virtuementioning
confidence: 99%